PENGARUH MEDIA PEMBELAJARAN QUARTET CARDS TERHADAP HASIL BELAJAR IPAS SISWA KELAS IV SEKOLAH DASAR - Azahra, Safira; Rufaida, Salwa; Nasharuddin, Nasharuddin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low learning outcomes in Natural and Social Sciences (IPAS) among elementary school students, as well as the suboptimal use of innovative learning media in the teaching process. Therefore, there is a need for instructional media that can enhance student engagement and understanding. This research aims to determine the effect of using Quartet Cards as a learning medium on the IPAS learning outcomes of fourth-grade students. The study employed a quantitative approach with a pre-experimental method using a one-group pretest-posttest design. The research subjects consisted of 29 students. The instrument used was a multiple-choice test. Data were collected through pretest and posttest and analyzed using descriptive and inferential statistics, including tests of normality, homogeneity, and paired sample t-test. The results showed a significant improvement in students’ learning outcomes. The average pretest score of 61.10% increased to 83.45% in the posttest. Hypothesis testing revealed a significance value of 0.000 (<0.05), indicating that the use of Quartet Cards has a significant effect on students’ IPAS learning outcomes. This study implies that game-based learning media such as Quartet Cards can effectively enhance student participation, motivation, and learning achievement.